1992
DOI: 10.1128/aem.58.11.3751-3758.1992
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Pseudomonas solanacearum-specific DNA probe by subtraction hybridization and construction of species-specific oligonucleotide primers for sensitive detection by the polymerase chain reaction

Abstract: A subtraction hybridization technique was employed to make a library enriched for Pseudomonas solanacearum-specific sequences. One cloned fragment, PS2096, hybridized under stringent conditions to DNA of 82 P. solanacearum strains representing all subgroups of the species. Other plant-associated bacteria, including closely related species such as Pseudomonas cepacia, Pseudomonas pickettii, or Pseudomonas syzygii, did not hybridize to PS2096. A minimum number of between 4 x 10i and 4 x 10' P. solanacearum cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…The detection limits for both sets of primers are in good agreement with those determined for other PCR-based detection systems for plant pathogenic bacteria (Seal et al 1992;De Boer and Ward 1995;Leite et al 1995;Smid et al 1995;Hartung et al 1996;Sulzinski et al 1996;Pan et al 1997;Zhang and Goodwin 1997), although some workers have reported even greater sensitivity (Seal et al 1993;Maes et al 1996). Detection limits may be further improved by the method of Hyman et al (1997) using prior enrichment of the organism on selective medium.…”
supporting
confidence: 80%
“…The detection limits for both sets of primers are in good agreement with those determined for other PCR-based detection systems for plant pathogenic bacteria (Seal et al 1992;De Boer and Ward 1995;Leite et al 1995;Smid et al 1995;Hartung et al 1996;Sulzinski et al 1996;Pan et al 1997;Zhang and Goodwin 1997), although some workers have reported even greater sensitivity (Seal et al 1993;Maes et al 1996). Detection limits may be further improved by the method of Hyman et al (1997) using prior enrichment of the organism on selective medium.…”
supporting
confidence: 80%
“…A 10-kb HindIII fragment containing DNA homologous to the vls locus of B. burgdorferi B31 was identi¢ed in B. garinii A87SA by genome subtractive hybridization [16]. Brie£y, DNA from strain A87SA (tester) was partially digested with Sau3A and hybridized to DNA from strain A87SB (driver) which had been sheared by ultrasonication [17]. The reassociated DNA mixture was ligated into a vector and resulting clones were tested for their reactivity with strains A87SA and A87SB.…”
Section: Cloning and Sequencing Of The Vls Locus Of B Garinii A87samentioning
confidence: 99%
“…Gene-based methods have proved very efficient to rapidly identify and detect the pathogens with high sensitivity and specificity. Designing and development of specific primers for identification and detection of R. solanacearum have already been reported by many workers (Seal et al 1992;Opina et al 1997;Boudazin et al 1999;Weller et al 2000;Wolf 2000;Schonfeld et al 2003). Most of the existing primers show positive signals to closely related species instead of specific detection of R. solanacearum.…”
Section: Discussionmentioning
confidence: 99%